Economic history of the iron and steel industry in the United States - Hogan, William Thomas (Lexington, Mass. : Heath, 1971)
This work deals with most phases including: development the iron and steel industry from 1860 to 1880; growth of the iron and steel industry; reorganisation of the iron and steel industry; market growth and new technology; the steel industry in depression and war; the steel industry in a period of world-wide challenge and fundamental change.
Set of vol.1-5
Includes bibliography and index
kjo 15/01/2019
Loans
Keywords: Iron industry and trade; Steel industry and trade; United states